Da’wah and Culture: Islamic Value in Sorong Serah Aji Krama in Padamara Village, East Lombok - Siti Nurul Yaqinah; Daeng Sani Ferdiansyah; Andri Kurniawan (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2021)
Sorong serah aji krama is one of the processions in the marriage custom of the Sasak people in Padamara Village, East Lombok, which is still preserved today. This study aims to explain the implementation and meaning of Islam in the sorong handover aji krama procession. This study uses a descriptive qualitative approach to the perspective of symbolic interaction through a case study research design. The results of this study revealed that there are Islamic meanings in sorong serah aji krama such as being a leader, close relations between religion and customs, husband's responsibility, affection and courtesy. The symbols in this procession are also seen in its implementation, each part reflecting self-awareness and the role of the family as heirs of values. This tradition also displays a close relationship between culture and religious teachings for the Sasak people in West Nusa Tenggara. This research has implications for the internalization of Islamic values in culture. thus strengthening the relation between religion and culture in the theological and sociological scope.Sorong serah aji krama merupakan salah satu prosesi yang ada dalam adat pernikahan masyarakat suku Sasak di Desa Padamara Lombok Timur yang masih dilestarikan sampai saat ini. Penelitian ini bertujuan untuk menjelaskan tentang cara pelaksanaan dan pemaknaan secara Islam pada prosesi sorong serah aji krama. Penelitian ini menggunakan pendekatan kualitatif desktiptif perspektif interaksi simbolik melalui desain penelitian studi kasus. Hasil penelitian ini terungkap bahwa terdapat makna secara Islam dalam sorong serah aji krama seperti menjadi pemimpin, hubungan erat agama dan adat, tanggung jawab suami, kasih sayang serta sopan santun. Simbol yang ada dalam prosesi ini juga terlihat dalam pelaksanaannya, setiap bagian mencerminkan adanya kesadaran diri dan peran keluarga sebagai pewaris nilai. Tradisi ini pula menampilkan keterkaitan yang erat antara budaya dan ajaran agama bagi masyarakat Sasak di Nusa Tenggara Barat. Penelitian ini berimplikasi terhadap internalisasi nilai-nilai Islam dalam budaya. sehingga memperkuat relasi agama dan budaya dalam lingkup teologis dan sosiologis.